SKEWED SEX RATIO IN PUNJAB-A DEMOGRAPHIC CATASTROPHE (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
Death is a tragedy in whatever form, at whatever time and in whatever way it lays its hands. Female foeticide is a unique form of violence against women. The word “abortion” has been derived from “abortus” which means “to take away” and truly, the  practice takes away the wholeness of a woman who resorts to taking away the life of her own unborn child. Twin pressures of ‘Family Planning’ and ‘Dowry’ have brought female foeticide to such shameful proportion that sex ratio has been declining fast in  India; more so in the state of Punjab and Union Territory of Chandigarh.  In wake of these developments, Five Head Priests of “Akal Takht”, the highest seat of Sikh religious authority in the Golden  Temple at Amritsar issued a “Hukumnama” (an edict) in April, 2001, preaching excommunication of those involved in this  heinous practice. The National Commission of minorities, too, has decided to take up the issue beginning with Sikhs and  Punjabis. The paper highlights the magnitude of problem along with suggestive measures for combating the menace.
Keywords: Female foeticide; Male; Female ratio; Hukumnama